Menelusuri Kepatuhan Pajak: Faktor-faktor Penentu dan Studi pada Wajib Pajak Orang Pribadi di Kabupaten Kudus - Muti’ah, Atikah Nafisatul; Budiman, Nita Andriyani; Afifi, Zaenal (Jurnal Akuntansi, 2024)
This study aims to analyze the effect of information transparency, modernization of tax service technology, tax sanctions, subjective norms, and trust in the government on tax compliance for individual taxpayers in Kudus Regency. The sampling technique used in this study was purposive sampling with a total of 445 respondents. This study used a quantitative method with primary data obtained through distributing questionnaires. The analytical method used in this research is PLS-SEM with SmartPLS software. The results of this study indicate that information transparency, modernization of tax service technology, tax sanctions, subjective norms, and trust in the government have a positive effect on tax compliance.